Fine-Scale Foraging Behaviour and Energy Expenditure of Nominally Herbivorous Coral Reef Fishes; a Comparative Analysis Across a Turbidity Gradient on a Coral Reef in the Solomon Islands - Bravenboer, Dominic (Auckland University of Technology, 2026)
Coral reefs are some of the most biodiverse habitats on Earth and provide numerous ecosystem services to humans. However, coral reefs worldwide are under threat from increasing anthropogenic impacts such as climate change, overfishing, and sedimentation from land use. Phase shifts from coral dominated habitats to macroalgal dominated habitats are becoming increasingly frequent. While coral reefs have some natural resilience to disturbance, and the coral-macroalgal phase shift may be reversible, it is thought that the resilience and potential for reversal of phase shifts is largely dependent on the complementary effect of different feeding functional groups of fishes. Reefs in which certain functional groups are overfished have far less resilience and tend to shift to a permanent macroalgal dominated state. The study of different feeding functional groups of reef fish in the context of anthropogenic disturbance is now therefore, more important than ever. Here we examine the foraging behaviour and energy expenditure of two fish with contrasting feeding functional groups on the fringing reef at Vavanga off Kolombangara Island in the Solomon Islands. This naturally turbid reef receives fluvial inputs resulting in a natural turbidity gradient, making an ideal proxy for studying the effects of anthropogenic turbidity and habitat degradation from land-use changes. Five sites were selected along this turbidity gradient, ranging from a highly turbid river mouth, to offshore reef with relatively high coral cover and clear water. Remote stereo video analysis was used to analyse fish movements in 3D which allowed in-situ estimation of energy expenditure and fine-scale foraging behaviour. The aim was to identify how these traits are influenced by increasing turbidity and potentially elucidate early behavioural warning signs of reef degradation. We found that the generalist detritivore Ctenochaetus striatus was relatively resistant to turbidity, showing no significant trends with water clarity. Furthermore, it appeared to prefer moderate turbidity levels, feeding consistently on the epilithic algal matrix (EAM) with increasing bite rates in relation to site turbidity, possibly due to eutrophication increased productivity in the EAM. This trend continues until the most turbid site where feeding ceases and energy expenditure increases. This implies a high turbidity threshold for this species, and we conclude that it would likely not be an ideal candidate for revealing early signs of degradation. The excavating Chlorurus bleekeri, a specialist consumer of endolithic microbes, was recorded feeding so infrequently that no assumptions could be made about the effects of turbidity or habitat composition on its foraging behaviour. Furthermore, it showed no response in energy expenditure to visibility or site. Thus, we conclude that this species is also not an ideal candidate for modelling the effects of elevated turbidity and degradation. This study highlights that some coral reef fish are relatively resistant to turbidity and subsequent shifts in habitat composition, and perhaps such species will be crucial for maintaining reef resilience in the face of anthropogenic disturbances. This research could be furthered by AI automation of 3D video analysis, allowing for more data to be gathered on a greater number of species.